Sosialisasi Kesehatan dan Keselamatan Kerja (K3) dan Penggunaan Alat Pelindung Diri (APD) Pada Sektor Informal di Sumbawa - Rafi'ah Rafi'ah; Ana Lestari; Iga Maliga; Asri Reni Handayani; Putri Adekayanti (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2024)
Informal sector plays a crucial role in the global economy, involving millions of workers worldwide. However, despite its significant contribution, workers in this sector often lack adequate Occupational Health and Safety (OHS) protection. Personal Protective Equipment (PPE), which serves to protect individuals from workplace hazards, is frequently not provided by business owners and is often used unsafely by workers. This program aims to enhance the understanding of business owners and workers regarding OHS and the importance of using PPE at work. The program involved business owners and workers in the informal sectors of agriculture, woodworking/furniture, and rice mills in Sumbawa, conducted in July 2024. The initiative covered the entire process from preparation to evaluation, employing methods of socialization and direct field application. Results indicated an increase in knowledge among business owners and workers about OHS and the use of PPE. Feedback from both business owners and workers was very positive.